2021
DOI: 10.3390/ijerph18084055
|View full text |Cite
|
Sign up to set email alerts
|

Hate Speech, Emotions, and Gender Identities: A Study of Social Narratives on Twitter with Trainee Teachers

Abstract: The objective of this study is, on the one hand, to analyse emotional responses to the construction of hate speech relating to gender identity on Twitter. On the other hand, the objective is to evaluate the capabilities of trainee primary education teachers at constructing alternative counter-narratives to this socially alive issue, surrounding the approval of the Ley de Identidad de Género [Gender Identity Law] in Chile, in 2018. With this two-fold objective in mind, quantitative, descriptive, and inferential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 62 publications
1
13
0
7
Order By: Relevance
“…In fact, the second relationship emphasized was between gender and pride: rs(100) = .672, p < .002, r 2 = .81, 1 − 𝛽 = .1. Addressing the inclusion of an unsatisfactory democratic gendered citizenship approach to expressing digital self-identity debates (Ortega-Sánchez et al, 2021), in this study we found a positive and proactive counternarrative. The TikTokers who were classified in this group explained their identity, or else how they found themselves, i.e., their experience in identifying their gender in a healthy and comfortable manner.…”
Section: Gender Identitymentioning
confidence: 57%
“…In fact, the second relationship emphasized was between gender and pride: rs(100) = .672, p < .002, r 2 = .81, 1 − 𝛽 = .1. Addressing the inclusion of an unsatisfactory democratic gendered citizenship approach to expressing digital self-identity debates (Ortega-Sánchez et al, 2021), in this study we found a positive and proactive counternarrative. The TikTokers who were classified in this group explained their identity, or else how they found themselves, i.e., their experience in identifying their gender in a healthy and comfortable manner.…”
Section: Gender Identitymentioning
confidence: 57%
“…Podemos establecer de manera coincidente, con estudios como los de Ballbé et al (2021) y de Izquierdo (2019), que el profesorado, como se ha visto en los resultados y datos, se mantiene alejado de una formación específica en didáctica adecuada que le permita trabajar los discursos del odio (Marolla-Gajardo, 2020;Ortega-Sánchez et al, 2021). Esto puede estar asociado a una formación inicial docente que no se enfoca en la formación de un profesorado que asume un rol activo para abordar, desde la enseñanza de las ciencias sociales, las problemáticas socialmente relevantes, o temáticas que apunten al desarrollo de la justicia social, considerando que el estudio se enfoca en las percepciones de los y las docentes sobre las y los estudiantes en torno a los discursos de odio en las aulas y la enseñanza de la historia y las Ciencias Sociales.…”
Section: Discusión De Los Resultadosunclassified
“…Desde las perspectivas de género en relación a los discursos de odio, es posible manifestar la necesidad de promover la perspectiva crítica y problematizadora en torno a las homogeneidades y las corrientes que buscan generar discriminaciones y continuar con la REIDICS, 11, 2022, pp. 52-67 reproducción de las estructuras hegemónicas patriarcales (Marolla-Gajardo, 2020;Ortega-Sánchez et al, 2021). Resulta necesario que se fomente el pensamiento crítico y reflexivo en relación a la lucha contra las desigualdades por razones de género e identidad.…”
Section: Discusión De Los Resultadosunclassified
“…Los modos, contextos y espacios de socialización y, por ende, de construcción de identidades se han ampliado. De hecho, en esta era digital, la ciudadanía europea está generando y construyendo identidades (Richardson y Milovidov, 2019) sin tener en cuenta sus derechos en línea (y los de las y los demás), así como la importancia de establecer comportamientos cívicos que no desarrollen y/o acrecienten discursos de odio (Ortega et al, 2021). Por eso es fundamental la formación en literacidad crítica digital en el futuro profesorado (Santisteban, Díez y Castellví, 2020), desarrollando competencias que les permitan actuar adecuadamente ante un fenómeno como son las redes sociales en la sociedad democrática (Pangrazio, 2016).…”
Section: Competencias Para Una Cultura Democrática ¿Qué Supone Desarr...unclassified